SYNTHESIS, STRUCTURE INVESTIGATION, SPECTRAL PROPERTIES AND IN VITRO ANTIOXIDANT EVALUATION OF NEW 1-(3-METHYL-3-MESITYL)-CYCLOBUTYL-2-(5-THIOPHEN-4-ETHYL-2H-11,2,4]TRIAZOL-3-YLSULFANYL)-ETHANONE - Orek, Cahit; Sarac, Kamiran; Parlak, Akif Evren; Koparir, Pelin; Turkoglu, Semra; Koparir, Metin (Parlar Research & Technology Ug, 2018)
The spectral analysis of 1-(3-Methy1-3-mesity1)-cyclobuty1-2-(5-thiophen-4-ethyl-2H-[1,2,4] triazol-3-ylsulfanyl)-ethanone (3) is carried out using the FT-IR, FT-NMR and UV-Vis spectra of the compound with the help of quantum computations by density functional theories. The recording of the FT-IR (40000 - 400 cm(-1)) spectra is done in solid phase, while the H-1 and C-13 NMR spectra and the UV spectrum (200-400 nm) are respectively recorded in the DMSO phase and the ethanol phase. According to the generated results, the reproduction of the crystal structural parameters and theoretical vibrational frequencies can be successfully achieved by the refined geometries. Furthermore, there is consistency between the H-1 and C-13 NMR chemical shift values and the data from the experiment. The different conformers of the compound and their minimum energies are studied by potential energy surface scan, using DFT//B3LYP/cc-pVDZ method. As the energy difference between the conformers was very small. To account for the chemical reactivity and site selectivity of the molecules, molecular electrostatic potential (MEPS) map has been plotted. The in vitro antioxidant activity of the newly synthesized compound was measured and found to exhibit significantly higher antioxidant activity.
Keywords: 1,2,4-Triazole; FT-IR; DFT; Antioxidant activity; Fukui descriptors